PERAN PENTING TENTANG KEPUASAN MASYARAKAT TERHADAP PENGGUNA PELAYANAN JASA WIFI INDIHOME PT .TELKOM KABUPATEN OKU TIMUR - Deviana Susanti; Wihana Wihana; Reka Malinda (Jurnal Signaling, 2023)
In this study entitled "The Important Role of Community Satisfaction with Indihome Wifi Service Users PT. Telkom East Oku Regency. This research is a form of collaboration and can appreciate the importance of service to the community, which in this case uses indihome internet services from PT. Telkom, which are very fast in process and very high quality and quality, especially for internet connections that have high speeds of up to 100 Mbps. This role is how much the community is satisfied as users of these services, because this is the key to success in all matters and is very influential in facing increasingly fierce and large competition in East Ogan Komering Ulu Regency. PT Telkom, in this case, is a service provider with the indihome brand through its subsidiaries. Indihome is a leading digital service that uses technology that is reliable in its field and one of the product innovations that is always adapted to various characters at the level of community needs, both low, medium and high class and all of that cannot be separated from technology which is very much needed right now, right? only business people and just users, namely in Digital technology which is now a mainstay as well as programs with the main goal of facilitating all matters so that they are completed quickly.